2010
DOI: 10.2225/vol13-issue6-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic antioxidants extraction from raspberry wastes assisted by-enzymes

Abstract: The effect of enzymatic hydrolysis on phenolic antioxidant extraction was studied in raspberry solid wastes. This by-product possesses high content of crude fiber (60%) and low values of protein, oil and ash. Raspberry fiber composition suggests that biocatalysts with cellulase, hemicellulase and pectinase activities would be useful for carrying out an enzymatically assisted antioxidant extraction. Hydro-alcoholic extraction was done using different commercial enzymes. Total phenol content and antioxidant acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 40 publications
(45 reference statements)
1
30
0
3
Order By: Relevance
“…Maier et al (2008) used mixture of pectinolytic and cellulolytic enzyme in the ratio of 2:1 to extract bioactive compounds (phenolic acids, non-anthocyanin flavonoids and anthocyanins) from grape pomace where obtained yields were higher compared with sulfite-assisted extraction. Extraction of phenolic antioxidant from raspberry solid wastes was increased by application of enzyme in hydro-alcoholic extraction compared with non-enzymatic control (Laroze et al, 2010). Gómez-García et al (2012) extracted phenolic compounds from grape waste using different types of enzymes, celluclast, pectinex and novoferm in EAE and found that novoferm had the strongest effect on phenolic release from grape waste.…”
Section: Enzyme-assisted Extraction (Eae)mentioning
confidence: 99%
“…Maier et al (2008) used mixture of pectinolytic and cellulolytic enzyme in the ratio of 2:1 to extract bioactive compounds (phenolic acids, non-anthocyanin flavonoids and anthocyanins) from grape pomace where obtained yields were higher compared with sulfite-assisted extraction. Extraction of phenolic antioxidant from raspberry solid wastes was increased by application of enzyme in hydro-alcoholic extraction compared with non-enzymatic control (Laroze et al, 2010). Gómez-García et al (2012) extracted phenolic compounds from grape waste using different types of enzymes, celluclast, pectinex and novoferm in EAE and found that novoferm had the strongest effect on phenolic release from grape waste.…”
Section: Enzyme-assisted Extraction (Eae)mentioning
confidence: 99%
“…Cell wall is a nanocomposite material surrounding each cell outside the plasmalemma, which forms a continuous extracellular matrix and from cell to cell, the skeleton of plant tissues. It corresponds to an assembly of biopolymers, mainly polysaccharides but also proteins and phenolic compounds (Arnous 2009). Another reported mechanism of improving the extraction is the direct enzyme catalyzed breakage of the ether and/or ester linkages between the phenols and the plant cell wall polymers (Laroze et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the extraction of valuable compounds from the plant tissues by pressing is never fully accomplished (Viskelis et al, 2009;Laroze et al, 2010;Bobinaitė et al, 2013). More recently it has been shown that red raspberry press cake extracts exhibit significant antioxidant, proapoptotic and antibacterial activity suggesting that raspberry press cake may be regarded as a potential resource of nutraceuticals (Četojević-Simin et al, 2015).…”
mentioning
confidence: 99%